Stages and Scenarios of Health Insurance Market Development in Uzbekistan. - Nodir kizi, Umurzakova Mo’tabarxon (International Journal of Psychosocial Rehabilitation, 2020)
This paper makes analyses of the research on health insurance. On this case, insurance market development was mentioned by research methodology. Therefore, statistical and theoretical bases were discussed on the research analyses. Conclusion, paper has identified outcomes and shortcomings of the analyses to make further research points.Keywords---  ,  ,